2013
DOI: 10.7860/jcdr/2013/6859.3467
|View full text |Cite
|
Sign up to set email alerts
|

Osteoarticular Tuberculosis-A Three Years’ Retrospective Study

Abstract: Introduction: Extra pulmonary TB can be encountered in various organ systems, like lymph nodes, serous cavities, genitourinary tract, skeletal. Musculoskeletal TB can cause significant functional impairment. The clinical symptoms are variable, pain and swelling being common symptomatology. Investigations for suspected cases include radiological imaging, histopathological examination, bacteriological examination, and polymerase chain reaction.The mainstay of treatment is multidrug antitubercular chemotherapy. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Various studies have been conducted for diagnosis of OATB by demonstration of tubercle bacilli ( Table III ). Needle aspiration is a sensitive technique and has high positivity rates for detection of AFB as observed in our study as well as by Arathi et al (75%) and Masood et al (63%) 16 , 17 . However, Mousa et al found a low rate (27%) of positivity for AFB in their study.…”
Section: Discussionsupporting
confidence: 82%
“…Various studies have been conducted for diagnosis of OATB by demonstration of tubercle bacilli ( Table III ). Needle aspiration is a sensitive technique and has high positivity rates for detection of AFB as observed in our study as well as by Arathi et al (75%) and Masood et al (63%) 16 , 17 . However, Mousa et al found a low rate (27%) of positivity for AFB in their study.…”
Section: Discussionsupporting
confidence: 82%
“…Tuberculosis (TB) is a global disease that caused an estimated 1.2 million deaths in 2018 and around 10 million new TB cases were reported globally in the same year, with the incidence being stable in the recent years as per World Health Organization (WHO) report 1 Osteoarticular tuberculosis is a common manifestation accounting for 10–15% of all extrapulmonary TB (EPTB) 2 , 3 cases and 1–4% of all TB cases 4 – 6 . The bone and joint TB is most often found in spine and weight bearing extremities resulting in neurological complications and joint destruction 7 .…”
Section: Introductionmentioning
confidence: 99%
“…However, in view of the recent developments in migration of refugees from Africa and Arabic countries to Europe, tuberculosis may become a more frequent entity in central and northern Europe in the future [ 4 ]. At present, osteoarticular tuberculosis accounts for 1–4.3% of all cases of tuberculosis [ 3 ]. In Germany, approximately 20% of newly diagnosed cases of tuberculosis had an extrapulmonary focus [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarticular tuberculosis accounts for 8.1% of newly diagnosed cases and is more common among patients of Asian or African origin. Tuberculous coxitis is thought to arise as a consequence of prior pulmonary tuberculosis through hematogenous spread of mycobacteria [ 3 , 6 ]. Retrograde lymphatic or contiguous dissemination are also possible but less common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation